Analysis of metaverse tools and their impact in educational contexts - Ordoñez Valencia, Maylee Lisbeth (2022)
This article aims to analyze the metaverse tools and their impact in educational contexts. It is framed in its thematic aspect in the line of Information and Communication Technologies (ICT), oriented towards the area of education. A qualitative paradigm methodology was chosen, with a deductive method, under a documentary, bibliographic, descriptive research modality, through the systematization and analysis of bibliographic sources, scientific articles, statistical reports and research works, which were the support Of the investigation. The analysis of the results was carried out through content analysis according to categories of research interest. A greater number of investigations was evidenced during the periods 2013-2016 and 2017-2019 compared to the last period 2020-2022, the most used tools being” Second Life” and” Open Sim”. The impact that these have had is established, highlighting within them, from the positive point of view, that: they allow the development of competences of knowing, doing, living together; stimulates multiple intelligences, self-confidence, playful learning, collaborative work, kinesthetic abilities. From the negative point of view: if they are used indiscriminately, they can affect physical abilities; cognitive exhaustion; technological dependency, and they can also be exclusive as they require a greater degree of knowledge and availability of technological equipment.